El servicio personal de los indios en la Nueva España 1521-1550 - Zavala, Silvio, 1909-2014.; Project Muse. (Colegio Nacional, 1984)
"Two more volumes of Zavala's extremely valuable work, organized topically as in the past and offering commentaries, digests, and descriptions of archival documentation, other primary sources, and pertinent secondary works. Each volume also includes documentary appendices, such as material related to the construction of Mexico City's cathedral (vol. VI, appendix C) and digests of documents held in the Municipal Archive of Saltillo and the Archivo del Ayuntamiento de Monterrey (vol. VII, appendix B). With these volumes, Zavala has extended his work to the point of Independence, and provided investigators in many specific specialties with a wonderful resource"--Handbook of Latin American Studies, v. 58.
t. 1. 1521-1550 -- t. 2. 1550-1575 -- t. 3. 1576-1599 -- t. 4. Suplemento a los tres tomos relativos al siglo XVI -- t. 5. 1600-1635 <pt. 2 > -- t. 6. 1636-1699 -- t. 7. 1700-1821.
Includes bibliographies and indexes.
Description based on print version record.
Keywords: Indians, Treatment of -- Mexico -- History; Indians of Mexico -- Employment -- History; Encomiendas (Latin America); Indians of Mexico -- Government relations; Electronic books